Pregabalin induces conditioned place preference in the rat during the early, but not late, stage of neuropathic pain. (6th March 2018) - Asaoka, Yuta; Kato, Takahiro; Ide, Soichiro; Amano, Taiju; Minami, Masabumi
Highlights: Pregabalin suppressed allodynia during the early and late stages of neuropathic pain. Pregabalin produced rewarding effects in the early stage of neuropathic pain. Rewarding effects of pregabalin disappeared in the late stage of neuropathic pain. Pain chronification extinguished the rewarding effects of pain relief by pregabalin. Extinguishment of rewarding effects may be due to dopaminergic system dysfunction. Abstract: The present study aimed to examine the rewarding effects of pain relief during the early and late stages of neuropathic pain using a conditioned place preference (CPP) test. Animal models of neuropathic pain were prepared by spinal nerve ligation in male Sprague–Dawley rats. Intraperitoneal and intrathecal injections of pregabalin (300 mg/kg and 100 μg/10 μL, respectively) suppressed allodynia in the von Frey test both 2 weeks (early stage) and 4 weeks (late stage) after nerve injury. Intraperitoneal and intrathecal injections of pregabalin induced CPP during the early stage of neuropathic pain, suggesting that the CPP test serves as an objective and quantifiable behavioral assay to assess the emotional aspect of pain relief. In contrast with the early stage of neuropathic pain, intraperitoneal or intrathecal injection of pregabalin did not induce CPP during the late stage of neuropathic pain. The extinguishment of the rewarding effects of pregabalin during the late stage of neuropathic pain is likely due to dysfunction of the mesolimbic reward system, although the possibility that neuronal mechanisms other than dysfunction of the mesolimbic reward system are involved in the extinguishment of pregabalin-induced CPP cannot be excluded. We previously reported that not only the dopamine release in the nucleus accumbens induced by intrathecal pregabalin injection but also that induced by sucrose intake were extinguished during the late stage of neuropathic pain. These findings, combined with the results of this study, suggest that pain chronification leads to dysfunction of the mesolimbic reward system.